Ethical Investment’s Visible Hand:: Methods and Transformative Potentials (The Macau Ricci Institute Journal, 2020)
The current economic model and praxis in the long run depletes social life and natural capital. With a globalization process steering off the rails and the national and international institutions seemingly impotent and incompetent, the influence of civil-societal movements may be the only option left to change a monetary-economic regime “that kills” (Francis, 2013, no. 53). "Money must serve, not rule!" (Francis, 2013, no. 58). To make this a reality, the human family has to "seek other ways of understanding the economy and progress" (Francis, 2015, no. 16). To reach this goal, overcoming the widespread responsibility gap within the financial system may begin by debunking the disastrous myth of the “invisible hand”, which helped to proliferate irresponsible behaviour. “It is particularly hard to keep agents in line when they have little responsibility for the problems they have caused. That is often the case in finance; bankers are rewarded for decisions long before the effects of these decisions are clear. Finally, even if the invisible-hand assumption were true, it would not be relevant to the modern financial world, in which governments imposed regulations run the monetary system and are usually among the largest participants in the financial market.” (Hadas, 2009, p. 41).